2010
DOI: 10.1007/s00213-010-2082-6
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the orexin/hypocretin system in ethanol conditioned place preference

Abstract: Rationale-Recent studies suggest that orexin/hypocretin is involved in drug reward and drugseeking behaviors, including ethanol self-administration. However, orexin's role in ethanolinduced seeking behaviors remains unclear.Objective-These studies examined the role of orexin in the acquisition and expression of ethanol conditioned place preference (CPP) using the orexin 1 receptor (OX1R) antagonist SB-334867.Methods-Effects of SB-334867 (0-30 mg/kg) on locomotor activity were determined in DBA/ 2J mice (Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 54 publications
4
37
1
6
Order By: Relevance
“…In a conditioned place preference paradigm, where mice are conditioned to associate a distinct chamber with experimenter-administered alcohol, the OX2R antagonist JNJ-10397049 attenuates the acquisition, expression, and reinstatement of alcohol conditioned place preference (Shoblock et al, 2011). This is in contrast to the OX1R antagonist SB-334867 which, with the same dose of experimenter-administered alcohol, has no effect on the acquisition of alcohol conditioned place preference and blocks expression only of a weak place preference, but not a moderate or strong one (Voorhees & Cunningham, 2011). This suggests that reward following alcohol intake is primarily mediated by the OX2R.…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 62%
“…In a conditioned place preference paradigm, where mice are conditioned to associate a distinct chamber with experimenter-administered alcohol, the OX2R antagonist JNJ-10397049 attenuates the acquisition, expression, and reinstatement of alcohol conditioned place preference (Shoblock et al, 2011). This is in contrast to the OX1R antagonist SB-334867 which, with the same dose of experimenter-administered alcohol, has no effect on the acquisition of alcohol conditioned place preference and blocks expression only of a weak place preference, but not a moderate or strong one (Voorhees & Cunningham, 2011). This suggests that reward following alcohol intake is primarily mediated by the OX2R.…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 62%
“…[199] this may have more to do with mediating the rewarding properties of addictive drugs than the appetitive or drug-seeking phase. This is supported by findings that OX 2 receptor antagonism using JNJ-10397049 reduces CPP for alcohol [116], while OX 1 receptor antagonism does not [200]. A more recent study has also found no change in OX 2 receptor levels following withdrawal from cocaine selfadministration [201].…”
Section: Target Selection: Sora or Dora?mentioning
confidence: 71%
“…[8][9][10][11]29) Thus, the rewarding effects of low-dose/long-term EtOH administration protocols, which may have clinical relevance by modeling the early phase of the progression to alcoholism, are unknown. To this end, we investigated the reward strength of low-dose EtOH using several dose-term regimens with a constant total dose.…”
Section: Discussionmentioning
confidence: 99%
“…Previous CPP studies have reported that EtOH (2 g/kg for 2 weeks, total dose of 8 g/kg) induced a preference for the chamber associated with its rewarding effects. [8][9][10][11] To assess the rewarding effects of lower doses of EtOH, we administered EtOH (1 g/kg/week) for 4 weeks (medium dose) or EtOH (0.5 g/kg/week) for 8 weeks (low dose) for a total dose of 8 g/kg in both groups. Furthermore, we used Acam, which suppresses alcohol reward preclusively following i.p.…”
mentioning
confidence: 99%